Extraterrestrial microspherules from Bajada del Diablo, Chubut, Argentina - Orgeira, Maria Julia (2017)
The Quaternary infilling of a circular structure located in Bajada del Diablo, Chubut Province, Argentina has been proposed as a crater strewn field in previous studies. Here we report the finding of about 65 microspherules collected in a trench excavated in the center of the structure. The majority of hand-picked specimens are single, but some of them exhibit compound forms. The single specimens are spherical with a mean size of 137 μm, whereas the more complex samples show peduncles and drop shapes. Dendritic crystal growth is recognized in the internal structure of some broken microspherules. Preliminary chemical composition from the surface and center of microspherules was determined by energy dispersive spectrometry employing EDS. Quantitative EMPA and XRD analysis indicate that the microspherules are mainly composed of Fe and O with magnetite, Fe0 with subordinate wüstite. Following consideration of possible anthropogenic and volcanic origins, these spherulites are ascribed to an extraterrestrial input. An accumulation rate of 47 microspherules per m2/yr is estimated for the studied sediments. This value is two orders of magnitude higher than the reference flux for cosmic dust estimated for the last 1 Ma in the Transantarctic Mountains. The microspherules might have been generated as a byproduct of asteroid entry in the atmosphere.